A Land Tenure Module for LSMS - Stein T. Holden; Daniel Ali; Klaus Deininger; Thea Hilhorst (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2016)
This paper proposes to fill the important gap in reliable and nationally representative land tenure data by including a Land Tenure Module (LTM) to be linked to multi-purpose household surveys such as the Living Standard Measurement Surveys (LSMS). Developing survey standards to generate globally comparable land data is important for generating data to be used in global and regional land governance monitoring initiatives (SDGs; LPI – UNECA; GLTN/ GLII; VGGT). The LTM can be a cost-effective way to provide data for evidence-based analyses that will help identify the areas where policy action can have the most significant and/or immediate impact, and help in sequencing and prioritizing policy interventions. The paper illustrates important issues that may be analyzed based on such a module in order to motivate its implementation and where the current state of knowledge is constrained by limited data access. To facilitate this integration, a generic LTM is proposed based on an assessment of existing tenure modules and lessons learned from surveys on land tenure. It introduces a basic structure including: (i) ownership and use of agricultural and non-agricultural land and immobile assets on the land, (ii) sources of land acquisition including inheritance, (iii) land transactions, (iv) formal and informal property rights, (v) investments on the land, (vi) land conflicts, (vii) legal knowledge, (viii) gender and property rights, (ix) perceptions of tenure security and (x) trust in land-related institutions.
Keywords: Q15; R33; 330; Land Tenure Module (LTM); Living Standard Measurement Surveys (LSMS); generic questionnaire